Towards a general theory of the stock market - John Fender (University of Birmingham, Birmingham Business School, 2016)
Although there are many stock market anomalies which the Efficient Market Hypothesis (EMH) finds difficult to explain, it also has its strengths, and so far no alternative hypothesis has been developed which can explain what the EMH explains but which can also do a better job in explaining the phenomena with which it struggles. It is argued that the way forward is to postulate that the stock market can be in one of three states: a fundamental state, in which share prices are determined as in the EMH, a bubble or bull market state, in which share prices are above their fundamental levels but continue to rise because asset holders expect to sell the shares at even higher prices in the future, and a bear market state, in which shares are held exclusively by 'irrational' agents and rational agents cannot exploit the overvaluation because of short-selling constraints. It is also argued that heterogeneous rational expectations may help explain some features of stock market behaviour.
Keywords: G1; 330; efficient market hypothesis; rational expectations; bubbles; bear markets; short-selling constraints